Carnitine supplementation attenuates myocardial lipid accumulation in long‐chain acyl‐CoA dehydrogenase knockout mice. Issue 6 (6th April 2013) - Bakermans, Adrianus J.; van Weeghel, Michel; Denis, Simone; Nicolay, Klaas; Prompers, Jeanine J.; Houten, Sander M.
Abstract: Purpose: Elevation of long‐chain acylcarnitine levels is a hallmark of long‐chain mitochondrial β‐oxidation (FAO) disorders, and can be accompanied by secondary carnitine deficiency. To restore free carnitine levels, and to increase myocardial export of long‐chain fatty acyl‐CoA esters, supplementation of L‐carnitine in patients has been proposed. However, carnitine supplementation is controversial, because it may enhance the potentially lipotoxic buildup of long‐chain acylcarnitines in the FAO‐deficient heart. In this longitudinal study, we investigated the effects of carnitine supplementation in an animal model of long‐chain FAO deficiency, the long‐chain acyl‐CoA dehydrogenase (LCAD) knockout (KO) mouse. Methods: Cardiac size and function, and triglyceride (TG) levels were quantified using proton magnetic resonance imaging (MRI) and spectroscopy ( 1 H‐MRS) in LCAD KO and wild‐type (WT) mice. Carnitine was supplemented orally for 4 weeks starting at 5 weeks of age. Non‐supplemented animals served as controls. In vivo data were complemented with ex vivo biochemical assays. Results: LCAD KO mice displayed cardiac hypertrophy and elevated levels of myocardial TG compared to WT mice. Carnitine supplementation lowered myocardial TG, normalizing myocardial TG levels in LCAD KO mice. Furthermore, carnitine supplementation did not affect cardiac performance and hypertrophy, or induce an accumulation of potentially toxic long‐chain acylcarnitines in the LCAD KO heart. Conclusion: This study lends support to the proposed beneficial effect of carnitine supplementation alleviating toxicity by exporting acylcarnitines out of the FAO‐deficient myocardium, rather than to the concern about a potentially detrimental effect of supplementation‐induced production of lipotoxic long‐chain acylcarnitines.